A modified approach based on bearing area curve for surface wear characterization. Issue 3 (24th January 2020) - Wang, Yun; Mao, Junhong; Lu, Suwen; Xu, Zhenying; Liu, Hong; Li, Ruitao
Abstract : Purpose: Wear greatly influences the machine lifetime, performance and reliability and its quantification is very important. This paper aims to propose a modified bearing area curve method by combining the theory of the bearing area curve, and the relocation technique to calculate wear accurately and efficiently. Design/methodology/approach: H13 steel was chosen as the material of wear pair, and the wear experiments were carried out at 50 N, 60 r/min for 20 min. The surface was measured before and after wear experiments. The relocation was made by comparing the mean lines (planes) of the unworn and worn surface profiles. The calculated results using the proposed method were compared with that of the surface profile method for a two-dimensional surface to validate its accuracy. The method was then applied for a three-dimensional (3D) wear analysis. Findings: The worn surface shows clearly displacement compared to the unworn surface and implies the importance of including relocation in the bearing area curve method. The results from the proposed method are 98 per cent close to that from the surface profile method, indicating that the method is accurate for wear evaluation. Originality/value: As no feature point or relocation mark is needed to calculate the relocation value using the proposed method, the method can be applied to mild to severe wear. Also, as the deviation of different scans does not affect the relocation calculation, and no matching and stitching is required, this method can be easily applied to a wide wear area and 3D surface wear analysis.